Efficacy and Safety of Vildagliptin Compared to Sulphonylurea in Patients with Type 2 Diabetes during Fasting in Ramadan - Pathan, Md Faruque; Amin, Md Feroz; Afsana, Faria; Rahim, Md Saghir Abdur; Sarker, Md Jahangir Alam; Ali, Tanvir Mobarak; Rahman, Md Mahfuzur; Hasan, Farzana (Journal of Bangladesh College of Physicians and Surgeons, 2016)
The objective of this study is to evaluate the efficacy and safety of vildagliptin compared to sulphonylurea (SU) in Type 2 Diabetes during Fasting in Ramadan. This was a prospective, observational cohort study, which enrolledpatients from Bangladesh. Patients aged >18 years with T2DM and HbA1c <8.5% were treated with vildagliptin or SU as add-on to metformin or as monotherapy for 16 weeks.The primary outcome of interest was to compare the proportion of patients with >1 hypoglycemic event(s) (HE) during fasting between the vildagliptin and SU groups. Changes in HbA1c, body weight and treatment adherence were also measured. Of the 100 patients enrolled, 97completed the study and 3 patients discontinued prematurely. Patients experiencing >1 HE(s) were fewer in the vildagliptingroup compared with SU group (4.3% vs. 8.2%; p=0.678). The reduction in HbA1c was 0.1% with vildagliptin from a baseline of 7.1%,however, there was no changewith SU from a baseline of 7.2% (between-treatment difference: 0.1%; p=0.600). A gain of 0.35kg and 0.08 kg was seen with vildagliptinand SUs treatment, respectively. Overall, the incidence of adverse events was similar betweenthe vildagliptin and SU groups (23.4% vs. 20.4%) with no new safety signals. The treatment with vildagliptin was associated with fewer hypoglycemic events compared with SU and was well tolerated in Muslim T2DM patients fasting during Ramadan. J Bangladesh Coll Phys Surg 2015; 33(3): 120-125